Motivación y desempeño por competencias de los colaboradores de Senati Iquitos año 2024 - Rengifo Panduro, Erwin (2024)
The objective of this study was to determine the relationship between motivation and competency-based performance of employees at SENATI Iquitos in the year 2024. The research is basic, explanatory, and has a quantitative approach. It corresponds to the descriptive correlational level, following the characteristics described by Hernández, Fernández, and Baptista (2014). A non-experimental and cross-sectional design was used, analyzing the variables as they are found in their environment without manipulation, with data obtained at a specific moment. The results show that the Pearson correlation analysis between motivation and performance revealed a coefficient of 0.284, indicating a positive but low correlation. However, the significance value (0.088) is greater than the conventional threshold of 0.05, suggesting that the observed relationship is not statistically significant. In conclusion, despite finding a positive correlation between the motivation and performance of the employees of SENATI Iquitos in 2024, this relationship is weak and not significant, rejecting the hypothesis of a significant relationship between the two variables. These results suggest the need to explore other factors that may influence employee performance and reconsider the strategies used to measure and improve both motivation and performance in this organization. This study underscores the importance of reviewing and adjusting methodologies and strategies to obtain a deeper understanding of the elements that truly impact job performance.